2017
DOI: 10.3389/fmicb.2017.01279
|View full text |Cite
|
Sign up to set email alerts
|

Conserved Transcriptional Responses to Nutrient Stress in Bloom-Forming Algae

Abstract: The concentration and composition of bioavailable nitrogen (N) and phosphorus (P) in the upper ocean shape eukaryotic phytoplankton communities and influence their physiological responses. Phytoplankton are known to exhibit similar physiological responses to limiting N and P conditions such as decreased growth rates, chlorosis, and increased assimilation of N and P. Are these responses similar at the molecular level across multiple species? To interrogate this question, five species from biogeochemically impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 151 publications
9
31
0
Order By: Relevance
“…The exception to this being the reduced expression of TCA cycle genes by P. minimum , which may help to explain the decrease in growth rate (Figure 1 ). A limited transcriptional response of the dinoflagellates has been observed in experiments with nutrient limitation (Harke et al, 2017 ) and elevated temperatures (Barshis et al, 2014 ). The limited transcriptional response to environmental perturbations may be largely explained by the underlying regulatory mechanisms of cell physiology occurring at the translational or post-translational level for an estimated ~73–90% of dinoflagellate genes (Lin, 2011 ; Murray et al, 2016 ).…”
Section: Resultsmentioning
confidence: 91%
“…The exception to this being the reduced expression of TCA cycle genes by P. minimum , which may help to explain the decrease in growth rate (Figure 1 ). A limited transcriptional response of the dinoflagellates has been observed in experiments with nutrient limitation (Harke et al, 2017 ) and elevated temperatures (Barshis et al, 2014 ). The limited transcriptional response to environmental perturbations may be largely explained by the underlying regulatory mechanisms of cell physiology occurring at the translational or post-translational level for an estimated ~73–90% of dinoflagellate genes (Lin, 2011 ; Murray et al, 2016 ).…”
Section: Resultsmentioning
confidence: 91%
“…Further, transcript-based studies have revealed information on the metabolic adaptations of phytoplankton to specific environmental conditions, such as light or nutrient availability (e.g., Moustafa et al, 2010;Beszteri et al, 2012;Dyhrman et al, 2012;Frischkorn et al, 2014;Liu et al, 2015a;Harke et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…N-deplete cultures were generated by first growing cells on L1 media with an N:P ratio of 2.4:1 (88 mM nitrate: 36 mM phosphate) analogous what has been previously described ( Harke et al, 2017 ). This lower ratio stoichiometrically limited cultures in nitrogen and at least three transfers were performed to ensure no carryover from higher nutrient full L1 medium.…”
Section: Methodsmentioning
confidence: 99%
“…However, while this approach is powerful, it typically requires a fairly good understanding of the underlying molecular mechanisms and genetic diversity of related genes to allow for the derivation of probes or primers. Other studies have applied less targeted, transcriptomic approaches to detect nutrient limitation in marine phytoplankton ( Hwang et al, 2008 ; Cooper et al, 2016 ; Harke et al, 2017 ), but analogous studies are more difficult in diverse natural assemblages for which genetic information is not necessarily available. Given this, our understanding of the degree and severity of nutrient limitation in the marine environment, especially at the induvial species and cellular level, remains poorly constrained.…”
Section: Introductionmentioning
confidence: 99%